Analysis of Nasolabial & Nasofacial Angles between Bengali & Manipuri Adult Males of Bangladesh: A Photo-Anthropometric Study (Bangladesh Journal of Medical Education, 2024)
Background: Photo anthropometry is the scientific procedure that comprise using photographs to deal with the study of different proportion of body parts and completed measures that differ broadly among racial groups. This study was done to found the photo-anthropometric difference by measuring nasolabial and nasofacial angles of external nose between Bengali and Manipuri adult male of Bangladesh.Materials and methods: This cross-sectional analytic study was conducted in the Department of Anatomy, Sylhet MAG Osmani Medical College, Sylhet from January 2022 to December 2022. Fifty (50) Bengali and fifty (50) Manipuri adult males ranging from 25 to 59 years age group were selected through convenient sampling. Photo-anthropometric methods were used for collecting data from Sylhet region. Values of the study were expressed as mean ± standard deviation. Two samples mean "Z" test was used to compare the results between groups.Results: Between the two ethnic groups Bengali and Manipuri, the angular dimensions of external nose, nasolabial angle (P ≤ 0.05) was significantly higher in Manipuri adult males. On the other hand, the nasofacial angle (P≤0.05) was significantly higher in Bengali adult males.Conclusion: The result of the present study will play an important role in Anatomy, Plastic Surgery, Forensic Medicine, Genetics and Anthropology for identifications, adopting corrective surgical procedures, preparing nasal models for different ethnicity group.BJME, Volume-15, Issue-02, July 2024: 52-59